A Highly Stable Organic Luminescent Diradical. (2nd March 2023) - Abdurahman, Alim; Wang, Jingmin; Zhao, Yihan; Li, Ping; Shen, Li; Peng, Qiming
Abstract: It is very challenging to obtain stable room‐temperature luminescent open‐shell singlet diradicals. Herein we report the first stable Müller's hydrocarbon TTM‐PhTTM with luminescent properties. Variable‐temperature electron paramagnetic resonance spectroscopy measurements and theoretical calculations show that TTM‐PhTTM has an open‐shell singlet ground state with a diradical character of 90 %. Because of a small singlet‐triplet energy gap, the open‐shell singlet ground state can be thermally excited to a triplet state. TTM‐PhTTM shows room‐temperature deep‐red emission in various solutions. Unusually high stability of TTM‐PhTTM was also observed owing to effective steric hindrance and spin delocalization. Our results are beneficial to the rational design and discovery of more stable luminescent diradical materials. Abstract : Variable‐temperature EPR measurements as well as theoretical calculations have been carried out on a highly stable room‐temperature luminescent Müller hydrocarbon. The results indicate that the hydrocarbon has an open‐shell singlet ground state with a diradical character of 90 %, with the small singlet‐triplet energy gap enabling thermal excitation to a triplet state.